Occupational exposure to anaesthetic gases and high-frequency audiometry. (September 2015) - Giorgianni, Concetto; Gangemi, Silvia; Tanzariello, Maria Giuseppina; Barresi, Gaetano; Miceli, Ludovica; D'Arrigo, Graziella; Spatari, Giovanna
Objectives: Occupational exposure to anaestethic gases has been suggested to induce auditory damages. The aim of this study is to investigate high-frequency audiometric responses in subjects exposed to anaesthetic gases, in order to highlight the possible effects on auditory system. Methods: The study was performed on a sample of 30 medical specialists of Messina University Anaesthesia and Intensive care. We have used tonal audiometry as well as high-frequency one. We have compared the responses with those obtained in a similar control group not exposed to anaesthetic gases. Results were compared statistically. Results: Results show a strong correlation ( p = 0.000) between left and right ear responses to all the audiometric tests. The exposed and the control group run though the standard audiometry analysis plays different audiometric responses up only to higher frequencies (2000 HZ p = 0.009 and 4000 Hz p = 0.04); in high-frequency audiometry, as all other frequencies, the attention is drew to the fact that the sample groups distinguish themselves in a significantly statistic way (10, 000 Hz p = 0.025, 12, 000 Hz p = 0.008, 14, 000 Hz p = 0.026, 16, 000 Hz p = 0.08). The highest values are the ones related to exposed subjects both in standard (2000 Hz p = 0.01, 4000 Hz p = 0.02) and in high-frequency audiometry (10, 000 Hz p = 0.011, 12, 000 Hz p = 0.004, 14, 000 Hz p = 0.012, 16, 000 Hz p = 0.004). Conclusion: Results, even if preliminary and referred to a low-range sample, show an involvement of the anatomic structure responsible for the perception of high-frequency audiometric responses in subjects exposed to anaesthetic gases.